Kritik Moderasi Beragama atas Rekognisi Ahmadiyah di Indonesia - Thania , Afifatul; Dara Ayu Shandina , Ayeesha; Fristiawati; Pradeta , Galuh Dwi; Renaldhy B. J. K, Muhammad; Muhammad Noor , Aditia (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
Religious moderation refers to an attitude or perspective that emphasizes balance and tolerance in religious life, particularly in navigating diversity across ethnicity, religion, race, and culture. In Indonesia, the Ahmadiyya sect has been widely rejected by the public and government authorities, largely due to its classification as deviant by the Ministry of Religious Affairs. The Indonesian government has officially prohibited the dissemination of Ahmadiyya teachings, a policy that has sparked divergent public responses. While some community groups supported the ban and demanded stricter enforcement, others viewed it as a violation of fundamental human rights, particularly the right to freedom of religion and belief. This article employs a qualitative literature review approach with a descriptive method to objectively present the facts surrounding the issue. It aims to offer a deeper understanding of how religious freedom can be upheld within a pluralistic society, and how constructive criticism rooted in the principles of religious moderation can address religious tensions. The study seeks to contribute to fostering a more tolerant and inclusive Indonesian society by proposing informed solutions to conflicts surrounding the recognition of minority religious groups.